Effect of cover crops on hysteresis and anisotropy of soil hydraulic properties - Polich, Nicolás Guillermo; Lozano, Luis Alberto; Villarreal, Rafael; Salazar, María Paz; Bellora, Guido Lautaro; Barraco, Miriam Raquel; Soracco, Carlos Germán (Elsevier, 2022)
No till is the main management system for soil conservation world-wide. In Argentina is frequently implemented in simplified crop sequences, which has negative effects on soil physical quality (SPQ). Among the suggested practices to preserve the physical fertility of soils under no till have been cited winter cover crops (CC). Generally, the estimation of pore distribution parameters and capacity SPQ indicators has been conducted from the relationship between water content (θ) and matric potential (h) obtained from desorption experiments. However, the water retention curve is considered as hysteretic. The objectives of this study were to incorporate the wetting curve (WWRC) to assess the impact of the incorporation of rye (Secale cereale L.) as CC on hydraulic properties in the first 10 cm of a Typic Hapludol and to analyze if the values are affected according to the sampling direction. The incorporation of CC increased the hysteretic behavior in the near and the medium saturation region. The sample direction did not affect significantly any capacity indicators, manifesting the isotropic character of the porosity. The inclusion of the WWRC analysis can give additional information when assessing the impact of different management on soil hydraulic properties.